(untitled) (JournalNX - A Multidisciplinary Peer Reviewed Journal, 2023)
The results of the study show that teaching materials have value as one of the materials that must be mastered by students as well as being a source or teacher’s reference in learning activities . Observing this, the teacher needs to have optimal mastery of teaching materials, as one of the basics in teaching students. There are many cases that occur in schools regarding the lack of inequality in the learning process as a consequence of a lack of understanding of teaching materials. Some cases that stand out are that learning in class is not conducive, teachers are often fixated on textbooks, teachers lack references in developing student abilities, and teaching materials are very limited to what teachers know and the literature available at school. Realities like this make learning activities less dynamic and students’ insights are very limited to what the teacher conveys and the activities facilitated by the teacher in learning.